1985
DOI: 10.1007/bf01868428
|View full text |Cite
|
Sign up to set email alerts
|

Resistance properties of the diluting segment ofAmphiuma kidney: Influence of potassium adaptation

Abstract: Chronic exposure to high potassium stimulates K+-secretory mechanisms in the diluting segment of the amphibian kidney (K+ adaptation). Since K+ net flux depends critically on the passive cell membrane permeabilities for K+ ions, cable analysis and K+-concentration step changes were applied in this nephron segment to assess the individual resistances of the epithelium and the K+ conductance of the luminal cell membrane. Experiments were performed in the isolated, doubly-perfused kidney of both control and K+-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The two cell clones are stable and their transepithelial electrical resistances and other cell properties are virtually independent of passage number. For obvious reasons (based on the assumption that a high transepithelial electrical resistance primarily reflects a low passive ion permeability of the paracellular pathway; [11]) the highresistance C7 cell clone is the most suitable for identifying resistance breakdown due to invasion of carcinoma cells. Experiments can be started at electrical resistances of above 4,000 Ω cm 2 down to 25 Ω cm 2 , the background resistance of the filter set-up.…”
Section: Discussionmentioning
confidence: 99%
“…The two cell clones are stable and their transepithelial electrical resistances and other cell properties are virtually independent of passage number. For obvious reasons (based on the assumption that a high transepithelial electrical resistance primarily reflects a low passive ion permeability of the paracellular pathway; [11]) the highresistance C7 cell clone is the most suitable for identifying resistance breakdown due to invasion of carcinoma cells. Experiments can be started at electrical resistances of above 4,000 Ω cm 2 down to 25 Ω cm 2 , the background resistance of the filter set-up.…”
Section: Discussionmentioning
confidence: 99%
“…The Malpighian tubule has a transepithelial resistance of 58 O×cm 2 , of which the resistance of the transcellular active transport pathway is 180 O×cm 2 and the paracellular resistance 85 O×cm 2 [13][14][15]. The paracellular resistance relative to the transcellular resistance is thus approximately 0.5 as in amphibian distal tubules or rabbit colon which are considered moderately tight epithelia [16,17]. The transepithelial voltage is 59 mV, lumen positive, again consistent with a moderately tight epithelium.…”
Section: Introductionmentioning
confidence: 85%
“…For example, the inward conductance is almost the same as that of heart muscle (Sakmann & Trube, 1984a;Kurachi, 1985), yet bigger than that of egg cell membranes (Ohmori, 1978;Fukushima, 1981). However, in these other channel types it was virtually impossible to detect any outward currents in the steady state since the channels rapidly closed upon depolarization (Kurachi, 1985 The K+ conductance of the apical membrane of the Amphiuma diluting segment is known to be sensitive to Ba2+ (Oberleithner et al 1985). From the present study, the mechanism of block has been shown to be dependent upon the concentration of barium and the transmembrane voltage.…”
Section: Discussionmentioning
confidence: 99%